CÉU-MEDIA - Local Inter-Media Synchronization using CÉU - Santos, Rodrigo C. M.; Lima, Guilherme F.; Sant'Anna, Francisco Sant; Rodriguez, Noemi de La Rocque (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
The semantics of current multimedia languages is informal and may lead to the development of ambiguous applications. In this paper we investigate the use of the synchronous language Ceu´ for programming local multimedia applications, in particular, those applications that can be described as a set of synchronized media objects. Ceu´ has a deterministic, concise and accurate semantics which, along with high-level programming constructs, makes the language an attractive alternative for developing multimedia applications. We also present Ceu´ -Media, a library for programming multimedia in Ceu´ . Ceu´ -Media implementation guarantees that the properties of the Ceu´ synchronous semantics are reflected in the multimedia presentation, ensuring inter-media synchronization. We compare the synchronization paradigm of Ceu´ with those of NCL and SMIL, and examine the implementation of representative use cases.